Safety of Inhaled Fluticasone Propionate Therapy for Pediatric Asthma - A Systematic Review - Muley, Prasad; Shah, Monali; Muley, Arti (Current Drug Safety, 2013)
Context and Aim: Asthma is a common problem in paediatric population. International treatment guidelines recognize the role of inhaled corticosteroids for asthma in young children. Inhaled fluticasone propionate is reported to have greater systemic effects like other corticosteroids. Limited data is available on safety of this drug when used for longer duration. So, we conducted a systematic review to study the effect of inhaled fluticasone propionate on adrenal suppression, growth and bone mineral density in paediatric patients. Design: A systematic review Methods: We searched for Randomized controlled trials in MEDLINE from January 2000 to December 2012. References of included study were hand searched. Information on study design, study population, drugs and dosage used, follow up period, measures used to evaluate safety and outcomes was abstracted independently by three reviewers. Details of Included Studies: In all included studies, participants were asthmatic children below 18 years and treated with fluticasone propionate. Minimum follow up considered was three months and should have measured HPA suppression or growth velocity or bone mineral density. Results: Total ten studies were included. Studies which had monitored HPA function varied in dosage of drug, mode of administration and duration. Inspite of that it has been observed that serum cortisol level is affected by fluticasone propionate, no significant effect on bone mineral density was reported with fluticasone propionate, but the sample size was inadequate and dietary calcium intake was not recorded. None of the studies reported any significant reduction in growth when inhaled fluticasone propionate was used for the treatment of asthma, but the baseline growth and final adult height attained were not assessed. Limitation: This systematic review included only free full text articles published in English. Only randomized controlled trials were included. Cohort studies were not included. Conclusion: With available evidences, the safety of inhaled fluticasone propionate cannot be questioned. This systematic review could not derive any significant adverse effect on HPA function, growth and bone mineral density in asthmatic children when used for long duration and followed for up to three months.
Keywords: fluticasone propionate